1996
DOI: 10.1093/hmg/5.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Genotype to Phenotype in Fibroblast-derived Transmitochondrial Cell Lines Carrying the 3243 Mutation Associated with the Melas Encephalomyopathy: Shift towards Mutant Genotype and Role of mtDNA Copy Number

Abstract: Transmitochondrial cell lines were isolated by fusing mtDNA-less rho degrees 206 cells with enucleated fibroblasts derived from four members of a pedigree carrying in their muscle varying proportions of the mutation at position 3243 in the tRNA(Leu(UUR)) gene associated with the MELAS encephalomyopathy. The mitochondrial transformants derived from an asymptomatic individual were all homoplasmic for wild-type mtDNA. The proportion of wild-type transformants derived from clinically affected members of the pedigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 33 publications
2
48
0
1
Order By: Relevance
“…On the other hand, the constancy with the donor age in the extent of variation observed in O 2 consumption rate within the population of transformants derived from each individual suggested that age alone was not a major factor in the observed variability. In view of the observed highly significant positive correlation between O 2 consumption rate and mtDNA content in the total transformant population, it is very likely that the heterogeneity in respiration capacity detected among the o cell transformants derived from the same individual reflected in part the very slow and variable process of repopulation of o cells with fibroblast-derived mtDNA, which has been described recently (43). However, it is also reasonable to assume that possible differences in nuclear gene content and/or activity among the recipient o cells (36) played a significant role in the observed variability in respiratory capacity among individual donor-derived transformants.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…On the other hand, the constancy with the donor age in the extent of variation observed in O 2 consumption rate within the population of transformants derived from each individual suggested that age alone was not a major factor in the observed variability. In view of the observed highly significant positive correlation between O 2 consumption rate and mtDNA content in the total transformant population, it is very likely that the heterogeneity in respiration capacity detected among the o cell transformants derived from the same individual reflected in part the very slow and variable process of repopulation of o cells with fibroblast-derived mtDNA, which has been described recently (43). However, it is also reasonable to assume that possible differences in nuclear gene content and/or activity among the recipient o cells (36) played a significant role in the observed variability in respiratory capacity among individual donor-derived transformants.…”
Section: Discussionmentioning
confidence: 82%
“…mtDNA Content and Growth Rate of Transformant Clones-It has been shown that the repopulation of o cells with exogenous mtDNA by mitochondria-mediated transformation can be slow and proceed at a variable rate, depending upon the donor cell type (43), the recipient cells, and other factors. It was, therefore, conceivable that a lower than normal mtDNA content of the transformants could have affected their respiration capacity, being responsible for the interclonal variability within the clone distribution from the same individual.…”
Section: Resultsmentioning
confidence: 99%
“…For disease-causing mutations it is common that only a portion of the mtDNA molecules harbours the mutation, leading to heteroplasmy. Experiments with transmitochondrial cells have shown that the proportion of 3243A > G mutant genomes must exceed approximately 90% before normal respiratory chain function is impaired, 14 indicating that cells harbouring 3243A > G are faced with negative selection at the cellular level if the heteroplasmy is higher than this threshold. At the host level, factors that would lead to negative selection include female infertility, miscarriages, female mortality before or during reproductive years, and psychosocial constraints imposed by the disease.…”
Section: Relative Fitness Of 3243a > G Carriers Ymentioning
confidence: 99%
“…High percentage levels of mutated mtDNA are associated with a biochemical defect at the cellular level and severe disease in patients. However, it is not clear whether the pathology is primarily due to high amounts of mutated mtDNA, 3 low amounts of wild-type mtDNA, 4 or a combination of both. To develop our understanding of this issue, we followed mtDNA disease progression in seven subjects, correlating the absolute amount of mutated and wild-type mtDNA with the histochemical defect.…”
mentioning
confidence: 99%